Perancangan Aplikasi Pengenalan Tokoh Penemu Benda-Benda Penting Di Dunia Berbasis Android Menggunakan Metode Sequential Search - Tonny, Tonny; Munthe, Ibnu Rasyid; Munandar, Musthafa Haris (MEANS (Media Informasi Analisa dan Sistem), 2021)
The inventor figures succeeded in contributing to people's lives and making people's lives developed with the findings of the inventor figures, but there are still many people who do not know and know the inventor figures, people only know the objects found by the inventor figures but do not know who the characters find the objects. that thing. The introduction of the inventor character is one of the reference materials that can be used to introduce the inventor character. In this day and age, android-based inventor character recognition applications are very efficient to use. In making a character recognition application, strings can be implemented for the word search process. String can be interpreted as an approach how to find the pattern of arrangement of string characters in other strings or part of the body of text. String has several algorithms, one of which is the Sequential Search algorithm where this algorithm is a very simple search algorithm that is carried out by comparing data one by one from a predetermined data set (Array) until the data is completed (found) or there is no match (not found). ). This inventor character recognition application is designed by utilizing the setudio android software. So that the application is easier to use and can be used independently anywhere and anytime.